IoT based Oxygen Availability Monitoring and Automatic Control System for Clinical Patients - Sunardi, Sunardi; Abdillah, Muhammad Sholihul (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
Oxygen is essential for human survival, comprising 2% of total body weight yet the brain consumes approximately 20% of the body’s oxygen. Oxygen deficiency in the brain causes hypoxia, potentially leading to irreversible damage, liver dysfunction, and even fatality. Ensuring stable oxygen delivery in healthcare facilities requires an efficient centralized oxygen system. According to Indonesia's Ministry of Health Regulation No. 4 of 2016, centralized systems must maintain an output pressure of 4-5 bar. This study addresses the challenge of ensuring uninterrupted oxygen supply by developing an automatic supply-switching system. Utilizing programmable logic controller (PLC) Outseal control and IoT-based monitoring, the system detects cylinder pressure levels, switches supply to cylinders with pressure > 4 bar, and provides real-time data on pressure, flow, and cylinder status via human machine interface (HMI) and the Haiwell Cloud smartphone application. Rigorous testing demonstrated high precision, with error rates of 0.18% for Pressure Sensor A, 0.079% for Pressure Sensor B, and 0.89% for the flow sensor. This innovation enhances reliability and safety in medical oxygen systems.